Qualidade de vida, envelhecimento e Aids: uma revisão integrativa - Lima, édija Anália Rodrigues de (2010)
The concept of life quality has been largely discussed in such a way to point out paradigms able to influence policies and practices. Investigations in this thematic have been developing since the immerging of the social medicine aiming to subsidize the public policies and social movements. Based on this evidence the World Health Organization, has been worried in defining and investigating the life quality of all peoples. Since the mid twentieth century, a fast elevation in the quantity of elderly in developing countries was realized, which have repercussion in the biggest concentration of elderly people in the population. Brazil at the same time that witnessed the dissemination of the HIV, provided the treatment for free with antiretroviral, and these drugs favored the survival, even by the less expressive clientele of the epidemy, like elderly people. According to the Ministry of Health, the entities which attend elderly have obligation to inform the competent authority of health any occurrence of elderly people with infect-contagious diseases. The study developed aimed: Investigate the contributions of the scientific studies published in periodic online, during the period between 2000 and 2008, which involve the thematic: life quality, aging and Aids for nursing; characterize the studies developed by the Brazilian nursing, ahead of the thematics life quality, aging and Aids, about the elements inherent to the study, like the origin of the research, methodological aspects, ethical aspects and the periodic of online publication; Summarize the scientific productions about life quality, aging and Aids selected ,, considering the category in which it was framed, the data of identification of the study, as well as the constitutive elements of the same, according to the instrument of data collection used . For the development of this study it was necessary the use of assumptions of the integrative review of the literature, proposed by Ganong in the decade of 1980. Its development consists on the possibility of proposing allowance for the implementation of changes which promote quality in the assistential conductions of nursing through models of research. It yet admits the building of considerable literature analyzes, also involving discussions about the methods and results of the publications. 46 scientific articles which approached the thematic s life quality, aging and Aids were revised. These studies were categhorized in four groups, which invoved the thematic s in a related mode , which were identified by the letters: QVE, IQVE, EA e IQVA. When orderint the presentation and discussion of data, threegroups were cited. The first calld group A, approached the information inherent to publications; the Group B, brought the discussion of data inherent to the authors of the researches; and the Group C, unfolded the contents immerged in several thematic approaches identified. It is high lighted the importance of searchin the integrality of knlowedge among the active professionals in the assistance and the active in the academies. It is believed that the study developed can contribute with the development of the attention to the health of the elderly person and of the people who live with the HIV/Aids. It is comprehended the necessity of instigating the development of other researches that can search answers for so many interrogatives.